Life history evolution in three-spined stickleback - Rahman, Abdul (2017)
A main challenge in evolutionary ecology is to elaborate the main ecological factors that vary in a study system and analyse how those factors shape the phenotype of organisms in their natural environment. These ecological variables can have complex effects since most life history traits are correlated. Here I examined the effects of ecological factors on life history traits, and the relationship among life history traits of North Uist three-spined stickleback, Gasterosteus aculeatus (hereafter stickleback). Both abiotic and biotic factors that are commonly measured in aquatic systems, and are known to vary greatly between North Uist lochs, were examined. The traits analysed were body size, age and size at maturation, proportion of fish over one year old, and the fecundity rate. My results showed that there was strong variation in water chemistry and inter-specific competition among the lochs on North Uist. Lochs on the west side of the island were characterised by higher sodium and calcium ion concentrations, higher pH and conductivity, and increased inter-specific competition. As a result, western populations had a faster absolute growth rate, larger body size, and a higher proportion of older fish, indicative of a longer life span. Although western populations had a larger body size, they tended to mature later with a smaller gonadosomatic index. They also favoured a larger number of eggs, but with a smaller egg size. Variations within population showed that larger females had greater fecundity but small egg size. Both plasticity and evolution appear to have contributed to these life history variations. Overall, variation in life history of North Uist stickleback was largely related to measures of resources availability and interspecific competition, except for egg size which was mostly associated with variation in predator density.